Assessing the economic cost of road traffic crashes in Saudi Arabia: potential savings from scaling up interventions - Spencer, Garrison; Alluhidan, Mohammed; Reithinger, Richard; Alsukait, Reem F.; Czapski, Radoslaw; Alamri, Adwa; Cetinkaya, Volkan; Alshehri, Fatimah; Dahdah, Said; Hamza, Mariam M.; Herbst, Christopher H.; Alghnam, Suliman (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to (1) assess the direct and indirect economic cost associated with road traffic crashes (RTCs) in Saudi Arabia in 2022; and (2) estimate the potential economic savings associated with scaling up the full implementation of three priority road traffic safety interventions (i.e., speed limit enforcement, seat belt enforcement, and a graduated licensing system for new drivers).MethodsA cost-of-illness approach was used to estimate the economic impacts of RTCs in Saudi Arabia in 2022. To estimate how scaling up the three priority interventions to improve road traffic safety in Saudi Arabia would impact the estimated economic costs of RTCs, we applied the International Road Assessment Program method to the data and modeled the interventions’ full enforcement.ResultsIn 2022, the estimated cost of RTCs was Saudi Riyal (SAR) 137.6 billion (USD 36.7 billion), equivalent to 3.3% of Saudi Arabia’s GDP. Indirect costs account for 70.2% of the total cost of RTCs, with morbidity-related costs driving most of the cost at 40.2%. Men make up the majority (88%) of road traffic injuries and fatalities in Saudi Arabia, resulting in a significant proportion of the total costs. We estimate that scaling up the three priority interventions could prevent 610 deaths and 3,823 injuries per year, resulting in total annual savings of SAR 14.6 billion (0.35% of GDP).ConclusionThe study underscores the significant costs associated with RTCs in Saudi Arabia and emphasizes the potential substantial economic savings achievable through scaling up existing interventions.